Queer theory, butch/femme identities and lesbian space - Eves, Alison (Sexualities, 2004)
Queer theory has been criticized for its textual focus and lack of attention to the structural and to everyday social practices. This article is part of a wider attempt to draw on the different strengths and insights of queer theory and qualitative social sciences. I identify areas of intersection between them which suggest potential ways of developing a queer sociology. The article considers the negotiation of gender and sexual identity categories at the level of individual butch and femme identity narratives. The concept of interpretative repertoires is used to theorize the ways in which lesbians are both positioned by and actively negotiate particular discourses. I am interested in the spatial aspects of the negotiation and contestation of identities and the article examines the ways in which particular interpretative repertoires produce butch and femme metaphorical and material spaces. The article draws on a concept of space as fluid, contested in meaning and created through social interactions. The achievement of lesbian visibility is examined as a strategic intervention in the establishment of subcultural space in which lesbian genders may be performed and read in specifically lesbian ways. Butch and femme aesthetics are examined as tactics in resisting heterosexual space and demanding lesbian presence.
Keywords: approches et analyses; discipline; genre; hétérosexisme; personnes lesbiennes; queer; ressource en ligne; sciences humaines; sociologie; systèmes d'oppressions